Pathological characteristics of thyroid glands from Japanese Black Cattle living in the restricted area of the Fukushima Daiichi Nuclear Power Plant accident. (16th July 2019) - Sasaki, Jun; Uehara, Megumi; Sato, Itaru; Satoh, Hiroshi; Deguchi, Yoshitaka; Chida, Hiroyuki; Natsuhori, Masahiro; Murata, Takahisa; Ochiai, Kenji; Otani, Kumiko; Okada, Keiji; Ito, Nobuhiko
Abstract: To study the effect of ionizing radiation on thyroid glands, 66 Japanese Black cattle residing in the restricted area of the Fukushima Daiichi Nuclear Power Plant in 2013–2017 were pathologically examined. There were no clinical symptoms of thyroid disease in these cattle. Three cases of goiter and seven of atrophy were found in two among the four farms examined. Cases of goiter exhibited normal morphological structure without mass or nodule formation in thyroid glands. Cellular atypia or capsular invasion of the follicular epithelium was absent. The estimated integrated dose of external radiation in goiter cases ranged from maximum 797 mSv to minimum 24 mSv. All lobules in the seven atrophic thyroid glands were affected, but pathological findings, such as inflammatory cell infiltration or stromal fibrosis, were not observed. The estimated integrated dose of external radiation in atrophic thyroids ranged from maximum 589 mSv to minimum 8 mSv. Immunohistochemical analysis of anti‐nitroguanosine and the TUNEL method in goiter and atrophic thyroid glands did not reveal any positive findings. The present study indicates that there was no significant relationship between a radiation effect and pathological findings in any thyroid glands.